Age-related differences in cerebral blood flow underlie the BOLD fMRI signal in childhood - Moses, Pamela; Hernandez, Leanna M.; Orient, Elizabeth (Frontiers in Psychology, 2014)
Functional magnetic resonance imaging (FMRI) has become a premiere technique for studying the development and neural mediation of a wide range of typical and atypical behaviors in children. While the mechanism of the blood oxygen level-dependent (BOLD) FMRI signal has been a focus of investigation in the mature brain, it has been largely unexamined in the developing brain. One critical component of the BOLD signal that has been noted to change with age is cerebral blood flow (CBF). Reports of CBF in children based on clinical radioactive tracing methods have found elevated CBF in childhood relative to adulthood, which could affect the BOLD response. This study used noninvasive arterial spin labeling (ASL) MRI to study resting state and activity-driven CBF in conjunction with the functional BOLD response in healthy children 8 and 12 years of age and in adults. Participants performed a finger tapping task to generate robust activation measured in the motor cortex. Quantification of resting state CBF demonstrated higher CBF in 8 year olds and in 12 year olds relative to adults. The absolute increase in CBF between baseline rest and peak response during the motor task was also higher in children compared to adults. In contrast, the relative increase of CBF above baseline, expressed as percent of CBF change, was comparable across groups. The percent of BOLD signal change was also stable across age groups. This set of findings suggest that along with elevated CBF in childhood, other component processes of the BOLD response are also in an elevated state such that together they yield a net BOLD effect that resembles adults. These findings are consistent with our previous examination hemodynamics in primary sensory cortex. Although the magnitude of the BOLD response appears consistent between childhood and adulthood, the underlying physiology and cerebrovascular dynamics that give rise to the BOLD effect differ between immature and mature brains neural systems.